CONSUMER BEHAVIOR TRADERSIN BASANOHI SANANA MARKET - Abd Rauf Wajo (Archipelago, 2020)
This study to reveal the activities of traders in the Basanohi Sanana traditional market. The study focuses on the behavior of traders in their trading activities in terms of buying and selling, pricing, customer service and others. Descriptive research method. With the results of the research, namely the Basanohi Sanan traditional market is not a market that implements buying and selling with the sharia system, but carries out conventional buying and selling activities. However, in carrying out trading activities at the Basanohi Sanana traditional market, it was found that some of the traders' behavior in the market applied trading behavior that was coherent with the values of Islamic teachings as the religion practiced by local traders.